Adolescent Medial Patellofemoral Ligament Reconstruction: A Comparison of the Use of Autograft Versus Allograft Hamstring. Issue 5 (15th May 2018) - Kumar, Nikhil; Bastrom, Tracey P.; Dennis, M. Morgan; Pennock, Andrew T.; Edmonds, Eric W.
Background: Recurrent patellar instability is commonly treated with medial patellofemoral ligament reconstruction (MPFLR), and the use of allograft in anterior cruciate ligament reconstructions has demonstrated inferior outcomes. Purpose: To compare the outcomes of allografts versus autografts in adolescent MPFLR for patellar instability. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective chart review was completed on patients younger than 18 years who underwent MPFLR for recurrent instability after failed nonoperative management over an 8-year period with a minimum 2-year follow-up. Patients were divided into autograft or allograft hamstring cohorts for comparison. Primary outcome measures were return to normal activity, incidence of redislocation/subluxation, pain, stiffness, other complications, and Kujala scores. Statistical analysis using unpaired t tests was performed, with an alpha value set at P < .05. Results: After criteria were applied, 59 adolescents (36 allograft, 23 autograft; 38 girls, 21 boys) with a mean ± SD age of 15.2 ± 1.7 years and a mean follow-up of 4.1 ± 1.9 years (allograft, 3.3 ± 1.1 years; autograft, 5.7 ± 2.1 years; P ≤ .001) were included. Seven patients had concurrent osteotomies (3 allograft, 4 autograft), 11 patients had concurrent loose body removals (5 allograft, 6 autograft), and 9 patients had concurrent lateral release (7 allograft, 2 autograft). Between groups, no significant difference was found in change between preoperative and most recent follow-up (mean, 1.2 ± 2.1) or rate of return to sports (mean, 73.3%). In total, 9 surgeries failed (3 allograft, 6 autograft). For the surviving grafts, a statistical difference in mean Kujala scores at final follow-up was noted (allograft, 92.7; autograft, 97.4; P = .02). Conclusion: We identified no significant differences in return to activity, pain score changes, and incidences of failure between patients undergoing MPFLR with allograft versus autograft. Although teenagers with surviving autograft MPFLR reported statistically higher Kujala scores, the mean score difference of 5 points was not clinically significant. It appears that using allograft tendon instead of autograft tissue for MPFLR in this teenage population does not adversely affect long-term outcomes.